Materialism, Financial Literacy, and Online Impulsive Buying: A Study on the Post Millennial Generation in a Pandemic Period - Mega Noerman Ningtyas; Amelindha Vania (Universitas Airlangga, 2022)
Objective: The research aims to ascertain the influence and examine the function of materialism (centrality, success, and pleasure) on impulsive online purchasing using financial literacy as a moderating factor. Design/Methods/Approach: The quantitative study uses the SEM analysis technique with the assistance of the SmartPLS 3.6 software. This research uses a purposive sampling strategy to choose 415 individuals. Sample criteria: 1) Minimum age of 17 years and maximum age of 25 years; 2) Online transaction including an impulsive buy. Google form is used to get the data. Findings: The findings indicated that materialism and impulsive online buying have a positive and substantial impact. The association between financial literacy and materialism could not be moderated. The association between financial literacy and impulsive online buying is nonexistent. However, the relationship between central, happiness, and success on materialism is significant. Originality: Materialism and financial literacy work together to impact impulsive internet purchase choices. During the pandemic, it was found that Malang's students' financial literacy did not have a significant influence on their buying habits. This suggests that disadvantaged students are nevertheless prone to impulsive internet purchases despite their materialistic outlook.